Establishing price and profit at Ehmke Seed - Ehmke, Tanner (Kansas State University, 2011)
The wheat industry has experienced significant changes in recent years due to extreme market volatility in commodity markets. The challenge for farmers, seed dealers, and seed companies, therefore, is to determine value and price amid a rapidly fluxuating market environment. Locally, seed dealers must price seed wheat at a level that is both fair to the farmer with consideration to their local cash market, and yet profitable to the seed company. Ehmke Seed in Lane County, Kansas, is one such seed dealer struggling with determining price in an ever-changing market environment. This study analyzes pricing models based on historical seed prices and the local cash grain market. Twenty-five years of seed wheat prices at Ehmke Seed were compared to local cash wheat and grain sorghum prices at the Garden City Cooperative Elevator in Garden City, Kansas, with a margin analysis conducted on the models with respect to Ehmke Seed’s cost of production. This study also provides a statistical analysis of the competing price models to compare their reliability. A more dependable method of pricing will help Ehmke Seed come to a better understanding of alternative marketing options for wheat, and serve as a basis to help understand how future wheat varieties, such as transgenic wheat, may potentially be priced in the future.
Keywords: Wheat; Seed; Certified; Price